Do good with your life and bring happiness to others - UMP, PNC (2020)
Always enrich your life by doing good deeds and aiding others. Aiding others is not limited to giving away riches or material things, but it is enough to lend a helping hand to ease the burden of the people around us. What matters is the commitment to help regardless of position or relation, and it is the intent that counts.